A Mediação Pedagógica em contextos de aprendizagem online - Gervai, Solange Maria Sanches (2007)
The introduction of new digital technologies such as the computer and the internet in the educational context brought a rising interest on how to deal with these technologies in learning contexts and on how to efficiently use these new tools when teaching. Prado and Martins (2002), Toschi (2003), Belloni (2002, 2003), Ramal (2002), Moran, Masetto and Behrens (2000), Anderson et al. (2001), Almeida (2001) among many other researchers, in the context of distance education, point out the importance of the new informational technology as allies for the implementation of online courses and for students and teachers to communicate and interact through the use of e-mails, forum discussion lists and chats among other tools that can even promote real time interaction. Prado and Martins (2002), Toschi (2003), Belloni (2003) and Ramal (2002) draw special attention to the necessity and and importance of the quality of teacher mediation, mainly when courses have as an aim to develop collaborative education, since many online programs focus on self-oriented tasks, leaving behind the importance of teachers mediation in the construction of students knowledge. Following a socio constructivist perspective the present research aims to analyse and describe different types of teacher mediation that occurred in a specific teacher mediation course, observing the results of students participation and their learning opportunities due to the different types of mediations. We believe the results of these analyses can contribute to generate parameters for teacher education and teacher educators. More specifically this qualitative research explores, describes and analyses the different types of mediation through the analysis of the materiality of the discourse of three teachers in different task dynamics: students individual tasks and mediation in forum discussion lists in the online course Práticas de Leitura e Escrita, developed and designed by Pontifícia Universidade Católica de São Paulo in the postgraduate department of Applied Linguistics to Language 10 Studies, that answered with this course a demand of the state department of education of São Paulo city. The analyses basically followed the concepts of the Hallidayan systemicfunctional grammar (1978, 1985, 1994). The instruments of analyses were specifically based on concepts related to two metafunctions: the interpersonal metafunction that is related to the use of the language to interact with other people and the experiential metafunction that is related to the language we use to talk about our experience of the world. For the interpersonal analyses we have used the model of the language of Appraisal developed by Martin and Rose (2003) and Martin and White (2005) and the concepts of transitivity by Thompson (1996/2004) to deal with the experiential metafunction. The results of the analyses have led us to identify that certain actions of pedagogical mediation can result in different students participation. It was also verified that certain teachers actions can create more opportunities for students to learn and to interact with other students and the teacher. Besides, the research has also led us to see that teachers leave almost no room for students to engage in interactions though the possibilities offered by the new digital devices. The research tries to show that a study and an understanding of the different forms of online mediation can be revealing, helping us to offer new ideas for pedagogical online actions